If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -360 = -30(-2b) Remove parenthesis around (-2b) -360 = -30 * -2b Multiply -30 * -2 -360 = 60b Solving -360 = 60b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-60b' to each side of the equation. -360 + -60b = 60b + -60b Combine like terms: 60b + -60b = 0 -360 + -60b = 0 Add '360' to each side of the equation. -360 + 360 + -60b = 0 + 360 Combine like terms: -360 + 360 = 0 0 + -60b = 0 + 360 -60b = 0 + 360 Combine like terms: 0 + 360 = 360 -60b = 360 Divide each side by '-60'. b = -6 Simplifying b = -6
| b^2n-16= | | -4x+9=14 | | 3x-27x^3= | | -3x+5=-22 | | 8(b-x)=6b+ax | | 3t-5=7t+t-15 | | 2x+9=3x-5 | | x^3+9x^2+5x+45=0 | | 6(x+3)=4(x+31) | | X^3-2x-11=0 | | 1000x^3y^3+216z^3= | | 4(c-2)=5(c-4) | | -4x-9=35 | | (x+2)-81=0 | | -3+16=5b-2-4b | | 20x^2-5y^2= | | 2(-3-4y)=-10 | | 5y+9=3(y-5)+7 | | 4y+2y-7=3y+11 | | 7-7=14r-8r | | -3x-4=-34 | | y=3x^2-14x+8 | | 10(a+8)=30 | | 7=4x-8 | | y=x^2-6x-5 | | (5x-8)=(4x+8) | | 8x=4x+16 | | 0.4(3x+6)=1.7-(x+2) | | 9.7x+36.34=-10.3x+35.36 | | x^5-4x^4-8x^3-32x^2-9x+36=0 | | -(5y+2)-(-4y-8)=6 | | 2a+36=5a |